The experiment of wind electric water pumping for salt farmers in remote area of Demak-Indonesia - S. Dio Zevalukito; Yohanes Baptista Lukiyanto; F. Risky Prayogo (International Journal of Applied Sciences and Smart Technologies, 2022)
Local villagers in the remote area of Wedung, Demak, northern of Central Java, Indonesia utilized special equipment called wind-pump for sea water lifting and circulating on salt production processes. The salt farmer has skill to produce, manufacture and maintain his own traditional wind-pump. In the windpump structure unit consisted of four blade horizontal axis windmill and reciprocating pump. This experiment study separated both windmill and pump by 50 meters. The pump was low speed centrifugal type pump. The windmill shaft was connected electrically to the pump shaft. The electric transmission components were an AC generator, diodes circuits and an DC motor. The experiment is carried out in a place that has the same characteristics as the original place at southern region of Bantul, Yogyakarta, Indonesia. The variation of experiment was pump head of 55 cm and 85 cm during 6 hours each variation. The average wind speed at the time of data collection at the head of 55 and 85 cm were 3.9 and 3.8 m/s. The volume flow rate and the volume produced by the pump during 6 hours of operation were 0.134 and 0.215 liter/s and 2901.6 and 4640.6 liters.